Bukharin and the Bolshevik revolution : a political biography 1888-1938 - Cohen, Stephen F. (New York : Vintage Books, 1975)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Boecharin, Nicolai; bolsjewisme